Improving the Accessibility of Frontline Services : For Quality Care Amidst Infrastructure and Resource Constraints - World Bank Group (World Bank, Washington, DC, 2019)
In low, and middle-income countries, distance and cost can keep people in rural communities from seeking and receiving care, even from the frontline health system. Even where public health facilities exist, these barriers, paired with (often justified) perceptions that the care available is low quality, can lead to extremely low use of available services, despite high need. Together, these forces create systemic gaps in essential health service coverage. To effectively engage rural communities in essential primary care, frontline health systems must develop innovative, locally-appropriate, and cost-effective approaches to staffing, logistics, and financing that overcome entrenched barriers to care.